2021
DOI: 10.1080/0144929x.2021.1872705
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing Netizen’s behavior through influencer intervention enabled by crowdsourcing – a case of reddit

Abstract: Social news sites have enabled news identification and its promotion through crowdsourcing and provided users with the capabilities to discuss topics. Compared to social media, social news sites are information-rich and possess their own social network. Reddit has been classified as a social news website and possesses similar characteristics to other websites in the domain. These include Slashdot, Digg, and StumbleUpon. This paper provides a broad analysis of spectators' sentimental (or emotional) behaviour su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Following the methodology of Yadav et al. (2021b, c), the research uses four machine learning-based classification and regression models to estimate the influence of social factors and features on attitude development and use intentions of new information technology/information systems (IT/IS).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the methodology of Yadav et al. (2021b, c), the research uses four machine learning-based classification and regression models to estimate the influence of social factors and features on attitude development and use intentions of new information technology/information systems (IT/IS).…”
Section: Methodsmentioning
confidence: 99%
“…The study utilized the method suggested by Yadav et al. (2021a, b and c) to cleanse the data thus eliminating non-American Standard Code for Information Interchange (ASCII) characters, emoticons, digits, punctuations, URLs, mentions, stop words and unnecessary spaces.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While Reddit communication remains entirely digital, Nevard (2018) [9] suggested that Reddit is a public sphere that extends beyond the boundaries of the Reddit environment and influences individuals as they interact with society at large. Yadav et al (2021) [10] highlighted the absence of marketing schemes on Reddit, as individual users can report spam. This feature of Reddit ensures the genuineness of the individuals by reducing incentives for profit and discouraging misaligned motivations.…”
Section: Background and Related Workmentioning
confidence: 99%